Financial behaviour and financial wellbeing of MSMEs actors: The role of financial literacy and cognitive factors - Abdur Rafik; Aghnia Setyaning Rahayu (Jurnal Siasat Bisnis, 2020)
That financial literacy and psychological characteristics are important determinants of financial decisions have long been recognized in the literature. By focusing on Micro Small Medium Enterprises (MSMEs), this study investigates the extent to which financial behaviour and financial well-being consisting of both financial security and financial anxiety can be explained by financial literacy and cognitive factors such as self-control, optimism, and deliberative thinking. Several demographic factors such as gender, age, educational background, and the length of engaging in MSMEs, as well as the characteristics of MSMEs such as industry and monthly sales turnover are functioned as control variables. Data were collected using a questionnaire that was purposively distributed to MSMEs’ actors and analysed using Partial Least Square-Structural Equation Modeling (PLS-SEM). In total, 155 samples were analyzed. The analysis shows that financial behaviour can be explained by deliberative thinking, financial security can be explained by financial literacy and optimism, while financial anxiety can be explained by self-control. Financial behaviour was also found to have a positive direct effect on financial security and financial anxiety. Thus, to improve the financial well-being of MSMEs’ actors, it may be necessary to improve their personal financial management skills that can lead to the positivity of financial behaviour.